Empagliflozin in heart failure with preserved ejection fraction with and without atrial fibrillation: research article - Filippatos, Gerasimos; Farmakis, Dimitrios; Butler, Javed; Zannad, Faiez; Ferreira, João Pedro; Ofstad, Anne Pernille; Iwata, Tomoko; Brückmann, Martina; Pocock, Stuart J.; Packer, Milton; Anker, Stefan (European journal of heart failure, 2023)
Aims Atrial fibrillation/flutter (AF) is common in heart failure (HF) with preserved left ventricular ejection fraction (LVEF) and associated with worse outcomes. Empagliflozin reduces cardiovascular death or HF hospitalizations and slows estimated glomerular filtration rate (eGFR) decline in patients with HF and LVEF >40%. We aimed to assess the efficacy and safety of empagliflozin in improving outcomes in patients with HF and LVEF >40% with and without AF. Methods and results In this pre-defined secondary analysis of EMPEROR-Preserved, we compared the effects of empagliflozin versus placebo on the primary and secondary endpoints and safety outcomes, stratified by baseline AF, defined as AF reported in any electrocardiogram before empagliflozin initiation or in medical history. Among 5988 patients randomized, 3135 (52%) had baseline AF; these patients were older, with worse functional class, more previous HF hospitalizations and higher natriuretic peptides compared to those without AF (all p < 0.001). After a median of 26 months, empagliflozin reduced cardiovascular death or HF hospitalization compared to placebo to a similar extent in patients with and without AF (hazard ratio [HR] 0.78 [95% confidence interval 0.66-0.93] vs. 0.78 [0.64-0.95], interaction p = 0.96). Empagliflozin also reduced total HF hospitalizations (HR 0.73 [0.57-0.94] vs. 0.72 [0.54-0.95], interaction p = 0.94) and annual eGFR decline (difference = 1.368 vs. 1.372 ml/min/1.73 m2/year, interaction p = 0.99) consistently in patients with and without AF. There was no increase in serious adverse events with empagliflozin versus placebo in patients with and without AF. Conclusions In patients with HF and ejection fraction >40%, empagliflozin reduced the risk of serious HF events and slowed the eGFR decline regardless of baseline AF.